Analysis of Risk Factors for the Nutritional Status of Toddlers Below the Red Line (BGM): A Case Study in Sungai Kakap Village, Kubu Raya Regency, West Kalimantan, Indonesia: Analisis Faktor Risiko Status Gizi Balita di Bawah Garis Merah (BGM): Studi Kasus di Desa Sungai Kakap, Kabupaten Kubu Raya, Kalimantan Barat, Indonesia - Wanda Supriatna; Dedi Alamsyah; Iskandar Arfan (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2024)
Background: Body weight below the red line (BGM) is a condition of malnutrition caused by low energy and protein intake from daily food for a long period of time. Based on data from the Kubu Raya Health Office in 2020, there were 216 cases of toddlers below the red line with the highest case of Sungai Kakap Health Center with a total of 43 cases. Objective: The purpose of this study was to analyze the risk factors for nutritional status in under-fives below the red line (BGM) (case study of Sungai Kakap Village, Kubu Raya Regency, West Kalimantan, Indonesia) in 2019. Methods: This is a quantitative study with a case-control design. The population in this study was the entire number of toddlers recorded in Sungai Kakap Village as many as 661 toddlers. The sample in this study were all BGM cases in Sungai Kakap Village as many as 15 cases and 30 controls. Data analysis using Chi-square test. Results: Research results of factors associated with the incidence of BGM are exclusive breastfeeding (p = 0.032; OR = 7, CI = 1.167 - 42), family income (p = 0.000; OR = 24.75 CI = 4.739 - 129.258), LBW (p = 0.006; OR = 9.33 CI = 1.593 - 54.672). The unrelated factors were education level, posyandu service, history of infectious disease and sanitation. Conclusion: Exclusive breastfeeding, family income and LBW are the main factors causing the incidence of LBW in Sungai Kakap village, Kuburaya district, West Kalimantan, Indonesia. It is important to continue and intensify education about exclusive breastfeeding through posyandu and health workers, conduct economic interventions such as direct assistance and job training to help low-income families who are at high risk of BGM and intensive monitoring and care of low birth weight infants is needed to prevent future malnutrition.